(untitled) (Journal of Engineering, 2011)
This work presents the simulation of a Low density Parity Check (LDPC) coding scheme with multiuserMulti-Carrier Code Division Multiple Access (MC-CDMA) system over Additive White Gaussian Noise (AWGN) channel and multipath fading channels. The decoding technique used in the simulation was iterative decoding since it gives maximum efficiency with ten iterations. Modulation schemes that used are Phase Shift Keying (BPSK, QPSK and 16 PSK), along with the Orthogonal Frequency Division Multiplexing (OFDM). A 12 pilot carrier were used in the estimator to compensate channel effect. The channel model used is Long Term Evolution (LTE) channel with Technical Specification TS 25.101v2.10 and 5 MHz bandwidth including the channels of indoor to outdoor/ pedestrian channel and Vehicular channel